Design of piezoelectric ZnO based catalysts for ammonia production from N2 and H2O under ultrasound sonication. (May 2022) - Peng, Fengping; Lin, Jingyuan; Li, Haozhen; Liu, Ziming; Su, Qihang; Wu, Zhe; Xiao, Yafeng; Yu, Hongbo; Zhang, Mingji; Wu, Chunzheng; Wang, Wei; Lu, Chunhua
Abstract: Using mechanical waste energy to drive the ammonia production from N2 and water under ambient conditions is of great significance yet still very challenging. In this work, we designed ZnO microrods and ZnO-Ag heterostructures that exhibited high activity, selectivity, and stability in the production of ammonia under ultrasound sonication. Combining the piezoelectric force microscopy (PFM), temperature programed desorption of N2 (N2 -TPD), electron spin resonance (ESR), electrochemical analysis with finite element numerical simulation, we found that the size and morphology of ZnO greatly impacted the shape deformation as well as the piezoelectric potential across the material, while the oxygen vacancies were essential for the adsorption and activation of N2 . Loading Ag NPs onto ZnO could further enhance the N2 fixation activity by generating local strain at the Ag-ZnO interface, enhancing the chemical adsorption of N2, and facilitating the separation of piezo-generated electrons and holes. Our work demonstrates the design principles of highly active piezoelectric catalysts for N2 fixation. Graphical Abstract: ga1 Highlights: ZnO and ZnO-Ag catalysts were designed for piezo-catalytic nitrogen fixation. They exhibited high activity, selectivity, and stability in the production of NH3 from N2 under ultrasound sonication. The morphology and surface oxygen vacancies of ZnO showed huge impact on the catalytic activity. Loading Ag nanoparticles on ZnO microrods could further improve the ammonia production rate.